Investigating asian weaver ants (oecophylla smaragdina) as biological control agents of bagworm outbreaks in oil palm plantation - Andreas Dwi Advento (2023)
Oil palm plantation is susceptible to lepidopteran pests, particularly bagworm. To cope with bagworm outbreaks, integrated pest management programs, in which insecticide use is minimised, are widely implemented to support sustainable oil palm production. However, there remain opportunities for improvement and innovation. This study aims to investigate the role of the Asian Weaver Ant (Oecophylla smaragdina ) as a predator of bagworm in oil palm plantations using monitoring censuses, experimental colony introductions in the field, and feeding trials of ant colonies in captivity. The study was conducted in plantations experiencing outbreaks of bagworm pests in Sumatra, Indonesia. Herbivory surveys in outbreak and nonoutbreak areas indicated that the abundance of weaver ant workers was positively influenced by availability of brood nest, the presence of colonies, palm canopy cover, and the age of the palms. The proportion of palms that were colonized by the weaver ant colonies increased with palm age and were higher in the areas without insecticide intervention. In a colony introduction experiment, colonies in palms with insecticide had a 273% higher risk mortality (Cox proportional hazards model, hazard ratio=3.735, p<0.001) than untreated palms. Insecticide treatment significantly reduced weaver ant abundance (t-test, t- value=-1.990, p=0.049), although there was no difference in leaf damage between palms with and without ant colonies. In a mass-rearing experiment, weaver ant colonies were propagated using four commercial protein food sources: tuna, mackerel, cricket and mealworm. Colonies fed tuna had smaller colonies. Colonies fed with cricket showed higher levels of aggression that those fed with mackerel. This study shows that the occurrence of weaver ants in plantations is influenced by the characteristics of the ant colonies, some environmental parameters and the use of systemic insecticides. To maintain weaver ant colonies in captivity, mass rearing method can be successfully used. These results of this study are likely to drive future improvement and innovation of IPM programmes in oil palm plantations.